Birthday Surprise - 18 Sexy Erotic Stories from Erika Lust - Wise, Marianne Sophia (Saga Egmont, 2023)
A deliciously sensual slice of birthday cake, \'Birthday Surprise - 18 Sexy Erotic Stories from Erika Lust\' is a collection of erotica that will give you a pleasurable treat worthy of birthday celebrations. From fantasies and voyeurism to summer flings, there\'s a sexy gift for every reader.